2001
DOI: 10.1248/bpb.24.1343
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Is Not Involved in the Entry of 67Ga into Hepatocytes from Regenerating Liver of Partially Hepatectomized Rats.

Abstract: Ga by the liver of the partially hepatectomized rats, suggesting that transferrin is involved in the uptake by the liver. However, 67Ga was taken up only slightly by hepatocytes obtained from the liver of these rats. We conclude that transferrin is involved in the uptake of 67 Ga by the liver tissue of partially hepatectomized rats but is not involved in its entry into the hepatocytes. Only a slight amount of gallium-67 enters the hepatocytes, and may accumulate primarily in the extracellular matrix of the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…2). This result was consistent with that of CCl 4 -treated rats, 9) and indicated that hepatocyte destruction occurred within 1 d after CCl 4 treatment.The uptake of 67 Ga by the liver tissue increased 1 and 2 d after the treatment (Fig. 3).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…2). This result was consistent with that of CCl 4 -treated rats, 9) and indicated that hepatocyte destruction occurred within 1 d after CCl 4 treatment.The uptake of 67 Ga by the liver tissue increased 1 and 2 d after the treatment (Fig. 3).…”
supporting
confidence: 90%
“…Hepatocytes were isolated from mice as described previously 18) : briefly, hepatocytes were isolated by a method in which the liver was perfused with collagenase (Nitta Gelatin, Osaka, Japan). The hepatocytes were counted with a well-type NaI-scintillation counter and the results expressed as cpm/1ϫ10 6 cells.…”
Section: Preparation Of Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently suggested that Tf-unbound 67 Ga was taken up into hepatocytes from CCl 4 -treated rat liver. 10) In the present study, we attempted to clarify detailed mechanism of Tf-unbound 67 Ga uptake by hepatocytes treated with CCl 4 using in vitro experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover we have reported that Tf is involved in 67 Ga uptake by the liver tissue but not in the entry of 67 Ga into the hepatocytes in partially hepatectomized rats. 13) In partial hepatectomy (PH), a part of the blood in circulation is lost together with removed liver tissues, consequently the blood cells and Tf in circulation decrease. Those decreases may cause enhances of the hematopoietic function in bone marrow and the number of Tf receptor (TfR) on various tissues.…”
mentioning
confidence: 99%